Xichú de Indios: marginality and the cultural frontier en Sierra Gorda, Mexico - Cisneros, Gerardo Lara (Locus: Revista de História, 2001)
The Sierra Gorda, a region in north-central Mexico, was a marginal zone in New Spain between the sixteenth and eighteenth centuries. It was also a cultural frontier between agricultural and hunter-gatherer communities. One of its villages, Xichú de Indios, was a place where different situations and factors converged (for example, multiple ethnic groups in an area of weak ecclesiastical and governmental authority). These factors led to a process of acculturation which resulted in an indigenous Identity characterized by religious beliefs that were syncretic, rebellious and contentious.